THE ANTIBACTERIAL EVALUATION OF HALICLONA ASSOCIATED BACTERIA AND THE RELATING COMPOUNDS DERIVED FROM THE HOST - Murniasih, Tutik; Putra, Masteria Yunovilsa; Hadi, Tri Aryono (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to investigate the active compounds derived from Haliclona sp. associated bacteria collected from Untung Jawa Island, Jakarta. Methods: The bacterial isolation, screening of antibacterial activity, purification, and prediction of potential compounds using liquid chromatography– mass spectroscopy/mass spectroscopy (LC–MS/MS) as well as 16S rDNA bacterial characterization were conducted. Results: The potential extract of bacterial strain UJ.17.10-4 showed the highest anti-Gram-positive bacteria. The 16S rDNA gene of this strain had 99% similarity with the actinobacteria Agromyces tropicus. Chemical separation of supernatant extract yielded 13 potent fractions. Identification of antibacterial compounds contained in active fractions using LC-MS/MS were halistanol sulphate C([M+H]+:703), cyclic bis-1,3- dialkylpyridinium([M+H]+: 213.72). In previous research reported that these compounds were isolated from Haliclona sponge and showed anticancer activity. Conclusion: This result supported the ideas that A. tropicus plays an important role in synthesizing, halistanol sulfate C, haliclorensin, and cyclic bis- 1,3-dialkylpyridinium metabolite derived from the host.